Effect of hot and cold petroleum ether extract of Olea europea olive leaves on the growth of some types of pathogenic bacteria. (Journal of the College of Basic Education, 2023)
The current study aimed at the effect of hot and cold petroleum ether extract of Olea europea olive leaves on the growth of four bacterial isolates, two isolates of Gram-negative bacteria Klebsiella sp. , Escherichia coli and two isolates of Gram-positive bacteria Staphylococcus epidermis, S. aureus. epidermis was the most effective with a diameter of inhibition (1.6, 1.4, 1.2, 1) cm and at concentrations (500, 250, 125, 62.5) mg/ml, while none of the four isolates showed any kind of inhibitory response towards the cold extract except for Klebsiella sp. With an inhibition diameter of (1) cm at a concentration of (500) mg/ml,The detection of flavones in the aforementioned extract showed the presence of the active substance in them.